Gabapentin treatment in olanzapine-induced restless legs syndrome： a case report - Gu Mengyue; Di Dongchuan; Qiu Jun; Zhai Jinguo (Sichuan jingshen weisheng, 2021)
The purpose of this study is to suggest the physicians using olanzapine to strengthen the recognition and treatment of restless leg syndrome （RLS） in clinical practice. In this paper， one patient with schizophrenia suffered from RLS during olanzapine administration， which was characterized by unpleasant sensory disturbances in bilateral lower extremity at night， intense urges to move legs， and inability to sleep. After taking gabapentin， the above symptoms were significantly improved.